(untitled) (Revista Direito em Debate, 2019)
Consecrated in article 5 of the Federal Constitution of 1988, fundamental rights, listed by the principle of human dignity, act as the foundation of the Democratic State of Law, but only effective are they become concrete in the life of society. The purpose of this article is to consider fundamental rights and their effectiveness, such as the fundamental right to religious freedom guaranteed in section VI of the above article and how they are implemented in the legal order of the country, verifying the treatment given to the issue by the national judiciary, always considering the laity of the Brazilian State. Therefore, the present, due to the relevance and contemporaneity of the theme, is justified by the search for the balance of the guarantee of religious freedom as a fundamental right, also analyzing the recent judgment regarding religious teaching, ADI 4439/2010. To do so, we will use the hypothetico-deductive methodology, qualitatively, collected in bibliographies and jurisprudence pertinent to the subject in question. It is concluded that the fundamental right to religious freedom and its fulfillment is the duty of the State, since it is incumbent upon it to guarantee equal right of choice and that, because it is secular, it should not have the attitude of favoring one or some religions, in order not to hurt the postulate in the Federal Constitution, thus guaranteeing the fundamental right to religious freedom and the dignity of the person in choosing his religion or belief.